Case Report: The JAK-Inhibitor Ruxolitinib Use in Aicardi-Goutieres Syndrome Due to ADAR1 Mutation - Cattalini, Marco; Galli, Jessica; Zunica, Fiammetta; Ferraro, Rosalba Monica; Carpanelli, Marialuisa; Orcesi, Simona; Palumbo, Giovanni; Pinelli, Lorenzo; Giliani, Silvia; Fazzi, Elisa; Badolato, Raffaele (Frontiers in Pediatrics, 2021)
Type I Interferonopathies comprise inherited inflammatory diseases associated with perturbation of the type I IFN response. Use of Janus kinase (JAK) inhibitors has been recently reported as possible tools for treating some of those rare diseases. We describe herein the clinical picture and treatment response to the JAK inhibitor ruxolitinib in a 5-year-old girl affected by Aicardi-Goutières Syndrome type 6 (AGS6) due to ADAR1 mutation. The girl’s interferon score (IS) was compared with that of her older brother, suffering from the same disorder, who was not treated. We observed a limited, but distinct neurological improvement (Gross Motor Function and Griffiths Mental Development Scales). Analysis of IS values of the two siblings during the treatment showed several changes, especially related to infections; the IS values of the child treated with ruxolitinib were consistently lower than those measured in her brother. Based on these observations we suggest that the use of ruxolitinib in children with the same condition might be effective in inhibiting type I interferon response and that starting this therapy at early age in children with AGS could mitigate the detrimental effects of type I interferon hyperproduction.